TRANSFORMASI INOVASI:PEMANFAATAN LIMBAH BATU BARA MENJADI PUPUK - Wentasari, Risa; Zadzali, Helmi; Sidiq, Egi Nur Muhamad; Anam, Khairul; Sridanti, Irma Lisa; Agusta, Herdhata; Sudradjat; Hariyadi; Bintoro, Mochamad Hasjim (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2024)
This literature study aims to review technological developments in the use of coal as fertilizer. The method used in this study is a systematic review. Article searches were carried out using Google Scholar with the keywords "Coal for Fertilizer" and "Pupuk Batu bara". At the end of the search, 14 articles were found consisting of 7 in Indonesian and 7 in English, then a narrative review was carried out. The conclusion of this study is that the use of coal as fertilizer was developed by utilizing low quality coal and coal waste: fly ash, bottom ash, humic acid and brown coal. The technology for using it as fertilizer is carried out by applying simple chemical and organic fertilizers together, or in the form of granular and slowrelease fertilizers.